Use of complementary and alternative medicine in children affected by oncologic, neurologic and liver diseases: a narrative review - Francesca Casini; Francesca Scaltrito; Maria Teresa Grimaldi; Tudor Lucian Pop; Valeria Calcaterra; Gian Vincenzo Zuccotti; Massimo Pettoello-Mantovani; Pietro Ferrara; Giovanni Corsello; Valentina Fabiano (BMC, 2023)
Abstract Complementary and alternative medicine (CAM) consist of a broad group of restorative resources often linked to existing local cultures and established health care systems and are also increasingly used in children with some serious illnesses. In this narrative review, we examine the epidemiology of the use, efficacy, and safety of complementary and alternative medicine in pediatric oncology, neurology, and hepatology. We searched for relevant articles published in Pubmed evaluating CAM use and its efficacy in safety in children affected by oncologic, neurologic and liver diseases. CAM is used to improve the success of conventional therapies, but also to alleviate the pain, discomfort, and suffering resulting from the diseases and their treatment, which are often associated with a significant burden of adverse effects. CAM use must be evaluated in children with neurological, oncological and liver diseases.